2002
DOI: 10.1002/jctb.567
|View full text |Cite
|
Sign up to set email alerts
|

Chemical neutralization of acidic wastes using fly ash in Israel

Abstract: Israeli¯y ash is highly basic when exposed to water, due to the very low sulfur content allowed in coal imports because of the strict environmental regulations (with respect to SO x emissions). Thus, the¯y ash is a potential chemical neutralization/®xation agent for acidic wastes. In this study, coal¯y ash has been examined as a neutralization/®xation agent for acidic sludge produced from the regeneration of used engine oils. The initial results show that the¯y ash can be used as a very ef®cient neutralization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…Fly ash is a low cost, environment friendly, unconventional and alternative adsorbent for activated carbon (Ceptin and Pehlival, 2007). It can remove different heavy metals from wastewater (Polat et al, 2002;Erol et al, 2005;Heechan et al, 2005). Researchers have reported that it can be used as pretreatment agent as an alternative to dolomite and limestone (Potgieter-Vermaak et al, 2006).…”
Section: Fly Ashmentioning
confidence: 99%
“…Fly ash is a low cost, environment friendly, unconventional and alternative adsorbent for activated carbon (Ceptin and Pehlival, 2007). It can remove different heavy metals from wastewater (Polat et al, 2002;Erol et al, 2005;Heechan et al, 2005). Researchers have reported that it can be used as pretreatment agent as an alternative to dolomite and limestone (Potgieter-Vermaak et al, 2006).…”
Section: Fly Ashmentioning
confidence: 99%
“…Studies have shown that fly ash was used to control the production of sulphaterich acid [8] and soil modification [9]. [10] and [11] successfully studied the removal of sulphates from acid mine drainage and acid leachate using fly ash and the research found that the removal was directly proportional to the fly ash CaO content (free lime content in the fly ash). The free lime in fly ash controls the acid generation from wastes as it releases the alkalinity to neutralise the acidity produced.…”
Section: Introductionmentioning
confidence: 99%
“…These authors observed that the coal fly ash controlled the acid generation from the wastes by release of alkalinity over time to the system which neutralized the acidity produced. Several authors have reported on the successful application of coal fly ash for inorganic contaminants removal from AMD and acidic leachates [8,19,30,31]. They observed that contaminants removal was directly proportional to CaO content of the fly ash.…”
Section: Introductionmentioning
confidence: 99%